2019
DOI: 10.1155/2019/2027947
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy in Fatigue Management in Multiple Sclerosis: An Umbrella Review

Abstract: Background. Fatigue is one of the most invalidant symptoms of Multiple Sclerosis (MS) that negatively affects occupational and work performance and social participation. Occupational therapy (OT) assessment and treatment of impairments related to fatigue can have a significant and positive impact on the quality of life. Methods. An umbrella review has been carried out to provide rehabilitative decision makers in healthcare with insight into the role of OT in fatigue management in Multiple Sclerosis. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…This multidimensional view of fatigue is consistent with variability across, and even within, an individual with MS and the significant impact on daily life (Billones et al, 2021). A tailored approach to assessment and intervention planning, considering primary and secondary potential causes of fatigue, is needed to support the self-management of fatigue (Connolly et al, 2013; Labuc, 2021; Salomè et al, 2019). Participants expressed physical fatigue descriptors (e.g., feeling run down, low battery), cognitive fatigue descriptors (e.g., jumbled, mental fog), and fatigue’s impact on participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multidimensional view of fatigue is consistent with variability across, and even within, an individual with MS and the significant impact on daily life (Billones et al, 2021). A tailored approach to assessment and intervention planning, considering primary and secondary potential causes of fatigue, is needed to support the self-management of fatigue (Connolly et al, 2013; Labuc, 2021; Salomè et al, 2019). Participants expressed physical fatigue descriptors (e.g., feeling run down, low battery), cognitive fatigue descriptors (e.g., jumbled, mental fog), and fatigue’s impact on participation.…”
Section: Discussionmentioning
confidence: 99%
“…Self-management programs, such as the Managing Fatigue Programme, are efficacious and effective in minimizing the impact of fatigue for pwMS (Finlayson et al, 2011; Ghahari et al, 2010; Mathiowetz et al, 2005; Packer et al, 1995; Salomè et al, 2019). This substudy draws on participant data from a larger study titled RE ducing F atigue and R estoring E nergy to S upport H ealth [REFRESH Study], which was funded by Patient-Centered Outcomes Research Institute, and was a large non-inferiority randomized clinical control trial.…”
Section: Introductionmentioning
confidence: 99%
“…During self-management interventions attention is focused on the ability to self-steer decision and actions, change behaviour and maintain emotional stability. 31,32 Based on a meta-analysis, the evidence of self-management programs in increasing quality of life (QoL) is however still limited. 33 demands.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Non-adherent to the treatment of MS may suggest being a major factor for the incidence of cognitive impairment and depression [16]. Depression is the main manifestation of the disease, which may be caused either by MS itself or its therapy as DMT [3,6]. On the contrary, a study reported that depressive symptoms occurrence are not likely to be associated with DMT but also some of them may decrease the incidence of depression [17].…”
Section: Introductionmentioning
confidence: 99%
“…It also can affect bowel and bladder function as well [ 5 ]. Additionally, the patient can present with physical and psychological symptoms, especially muscle weakness, balance problems, fatigue, and other depressive symptoms [ 3 , 6 ]. Depressive symptoms are common in patients with MS, and the pathogenesis is multifactorial.…”
Section: Introductionmentioning
confidence: 99%